Human brain tumor imaging with a protein-binding MR contrast agent: initial experience - Essig, Marco; Rohrer, Martin; Giesel, Frederik L.; Tüttenberg, Jochen; Weber, Marc-André; Michaely, Henrik J. M.; Gerigk, Lars; Voth, Matthias (European radiology, 2010)
Gadofosveset is a Gd-based protein-binding blood pool agent with increased relaxivities and blood half-life compared with conventional Gd-based contrast agents (GBCAs). No experience exists about the use of gadofosveset as an extracellular agent. In this report we present the first clinical experience with gadofosveset in enhancing intracranial tumors. Ten patients with different intracranial tumors were examined with a standard dose (0.03 mmol/kg) of gadofosveset compared with a standard dose (0.1 mmol/kg) of conventional GBCA. As a result of its significantly higher relaxivity, gadofosveset could, despite its low dose, achieve a sufficient contrast enhancement. The visual rating of the intensity of enhancement and the contrast to noise ratios were comparable to conventional agents. The detection and delineation of more complex lesions was rated equal. In one nonenhancing low grade astrocytoma an enhancing nodule became visible only 5 h after gadofosvesest injection. As shown in this initial report, contrast-enhanced intracranial tumor imaging is possible with the protein-binding blood pool agent gadofosveset. The agent gives a significant tumor contrast in early postcontrast imaging comparable with conventional agents. As a result of its unique longer lasting contrast, the use of gadofosveset might enable a new approach to imaging mild or nonenhancing tumors.